Subtoxic Alterations in Hepatocyte-Derived Exosomes: An Early Step in Drug-Induced Liver Injury? - Holman, Natalie S. (Toxicol Sci, 2016)
Drug-induced liver injury (DILI) is a significant clinical and economic problem in the United States, yet the mechanisms that underlie DILI remain poorly understood. Recent evidence suggests that signaling molecules released by stressed hepatocytes can trigger immune responses that may be common across DILI mechanisms. Extracellular vesicles released by hepatocytes, principally hepatocyte-derived exosomes (HDEs), may constitute one such signal. To examine HDE alterations as a function of drug-induced stress, this work utilized prototypical hepatotoxicant acetaminophen (APAP) in male Sprague-Dawley (SD) rats, SD rat hepatocytes, and primary human hepatocytes. HDE were isolated using ExoQuick precipitation reagent and analyzed by quantification of the liver-specific RNAs albumin and microRNA-122 (miR-122). In vivo, significant elevations in circulating exosomal albumin mRNA were observed at subtoxic APAP exposures. Significant increases in exosomal albumin mRNA were also observed in primary rat hepatocytes at subtoxic APAP concentrations. In primary human hepatocytes, APAP elicited increases in both exosomal albumin mRNA and exosomal miR-122 without overt cytotoxicity. However, the number of HDE produced in vitro in response to APAP did not increase with exosomal RNA quantity. We conclude that significant drug-induced alterations in the liver-specific RNA content of HDE occur at subtoxic APAP exposures in vivo and in vitro, and that these changes appear to reflect selective packaging rather than changes in exosome number. The current findings demonstrate that translationally relevant HDE alterations occur in the absence of overt hepatocellular toxicity, and support the hypothesis that HDE released by stressed hepatocytes may mediate early immune responses in DILI.